A forensics acquisition method of WhatsApp data on Android smartphone - Muzakir, Ummu Khosyatillah (2018)
Technology evolution in mobile devices and smartphones are kept progressing in demand. The environment of mobile devices is defined as personal usage; isolating the security priority at very beginning. Prior to the reason, it becomes a daring new target for the cybercrimes. WhatsApp application known as most widely used for communication platform, as well as a bold aim to perform mischiefs. Thus in this thesis, we propose the forensically sound method of data acquisition and analysis of WhatsApp application on Android smartphone. We will form guidelines on how forensic investigators extract the artifacts from WhatsApp. By having the artifacts, forensic investigators enable to describe on how the artifacts can be generated, describe relationship of the artifacts and the analysis can be done. The results gained by the method proposed in this thesis are at par with popular mobile forensic tools such as Cellebrite.